2013
DOI: 10.1002/fuce.201200214
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Perfluorosulfonate‐Free Phosphosilicate Glass‐Based Composite Proton‐Exchange Membrane

Abstract: Based on hydrothermally treated phosphosilicate (SiO2–P2O5) glass and sulfonated poly(ether ether ketone) (SPEEK) polymer, perfluorosulfonate‐free SiO2–P2O5/SPEEK composite membranes are prepared. The morphology, thermal and mechanical properties, pore structure, proton conductivity, water uptake, as well as the fuel cell performances of the SiO2–P2O5/SPEEK composite membranes are investigated. The SiO2–P2O5/SPEEK composite membranes with proton conductive SiO2–P2O5 glass powders of more than 50 wt.% were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The sol-gel synthesis of mixed oxide materials containing SiO 2 and P 2 O 5 has recently attracted great attention as a consequence of their functional properties. In fact, these materials nd applications as proton exchange membranes in fuel cells, [1][2][3][4][5] bioactive materials [6][7][8][9] and exhibit very interesting surface acidic properties, making them very attractive as solid acid catalysts. 10 Diverse protonic conduction abilities as well as Brønsted acid site distributions were found in these materials as a consequence of the variation in the Si/P molar ratio 11 and the preparation procedure 10 altering the distribution of P-species in the siloxane network.…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel synthesis of mixed oxide materials containing SiO 2 and P 2 O 5 has recently attracted great attention as a consequence of their functional properties. In fact, these materials nd applications as proton exchange membranes in fuel cells, [1][2][3][4][5] bioactive materials [6][7][8][9] and exhibit very interesting surface acidic properties, making them very attractive as solid acid catalysts. 10 Diverse protonic conduction abilities as well as Brønsted acid site distributions were found in these materials as a consequence of the variation in the Si/P molar ratio 11 and the preparation procedure 10 altering the distribution of P-species in the siloxane network.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the output power of the fuel cell using the composite membrane 7SPEEK/3(PeSi) is not only significantly higher than that of the cell using pure SPEEK, but also slightly higher than that of cell equipped with Nafion 212 membrane, which is probably because the composite membrane has higher proton conductivity under the measurement conditions. Moreover, the peak power density of the cell using 7SPEEK/3(PeSi) membrane is much higher than the value of 20.8 mW cm À2 released by a fuel cell based on phosphosilicate glass and the value of 355.6 mW cm À2 released by a fuel cell based on the composite membrane of SPEEK and phosphosilicate powders [20,35]. The main reason is probably that the composite membrane 7SPEEK/ 3(PeSi) obtained in this study shows a better flexibility; and therefore, it could endure adequate hot-pressing to acquire better interfacial contacts between the electrolyte membrane and the GDE without causing cracks in the membrane when assembled, which is of great importance for obtain high output power.…”
Section: H 2 /O 2 Single Fuel Cell Testmentioning
confidence: 90%
“…Our previous study showed that phosphosilicate glass possessed an excellent conductivity of above 10 À1 S cm À1 and we also reported a composite membrane based on phosphosilicate glass powders and SPEEK [19,20]. Although the composite membrane displayed relatively good proton conductivity and fuel cell performance; however, the mechanical properties of the composite membrane was affected seriously by the direct incorporation of phosphosilicate powers, insufficient to meet the needs of practical applications.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations